Students' Creative Thinking in STEM Integrated Project-Based Learning (PjBL-STEM) - Raras Setyo Retno; Purnomo; Arif Hidayat; Aynin Mashfufah; Enik Chairul Umah (Journal of Education Reseach and Evaluation, 2025)
The STEM Project-Based Learning (PjBL-STEM) model enhances students' creative thinking skills, allowing them to explore their potential and design projects accurately. This study aims to analyze students' creative thinking skills (originality) through the PjBL-STEM model, with a case study of 23 fourth-grade students at SDN Balongdowo, Sidoarjo. The research method used is qualitative to describe student activities based on creative thinking within the PjBL-STEM framework, with data collection techniques in the form of observation, interviews, and documentation. Data analysis was carried out descriptively and qualitatively. The PjBL-STEM project involved the design of a wind-powered vehicle that included activities such as understanding the mechanism of kinetic energy, energy transformation, brainstorming, and completing worksheets related to vehicle assembly for wind-powered motion trials. Students learned to design vehicles that adopted the concept of kinetic energy by utilizing wind power. The results showed that the analysis of students' creative thinking (originality) produced several findings: students independently created and designed projects with asymmetrical but accurate results, with very good criteria; students provide answers in their unique ways, perform calculation processes accurately, explore new methods, and complete projects with varying degrees of accuracy. This study concludes that the PjBL-STEM model effectively encourages students' creative thinking skills, especially in terms of originality, and has implications for improving the implementation of STEM-based learning to encourage innovation and creativity in elementary education.